Rearrangement of mitochondrial pyruvate dehydrogenase subunit dihydrolipoamide dehydrogenase protein–protein interactions by the MDM2 ligand nutlin‐3. Issue 17 (September 2016) - Way, Luke; Faktor, Jakub; Dvorakova, Petra; Nicholson, Judith; Vojtesek, Borek; Graham, Duncan; Ball, Kathryn L.; Hupp, Ted
Abstract : Drugs targeting MDM2's hydrophobic pocket activate p53. However, these agents act allosterically and have agonist effects on MDM2's protein interaction landscape. Dominant p53‐independent MDM2‐drug responsive‐binding proteins have not been stratified. We used as a variable the differential expression of MDM2 protein as a function of cell density to identify Nutlin‐3 responsive MDM2‐binding proteins that are perturbed independent of cell density using SWATH‐MS. Dihydrolipoamide dehydrogenase, the E3 subunit of the mitochondrial pyruvate dehydrogenase complex, was one of two Nutlin‐3 perturbed proteins identified fours hour posttreatment at two cell densities. Immunoblotting confirmed that dihydrolipoamide dehydrogenase was induced by Nutlin‐3. Depletion of MDM2 using siRNA also elevated dihydrolipoamide dehydrogenase in Nutlin‐3 treated cells. Mitotracker confirmed that Nutlin‐3 inhibits mitochondrial activity. Enrichment of mitochondria using TOM22+ immunobeads and TMT labeling defined key changes in the mitochondrial proteome after Nutlin‐3 treatment. Proximity ligation identified rearrangements of cellular protein–protein complexes in situ. In response to Nutlin‐3, a reduction of dihydrolipoamide dehydrogenase/dihydrolipoamide acetyltransferase protein complexes highlighted a disruption of the pyruvate dehydrogenase complex. This coincides with an increase in MDM2/dihydrolipoamide dehydrogenase complexes in the nucleus that was further enhanced by the nuclear export inhibitor Leptomycin B. The data suggest one therapeutic impact of MDM2 drugs might be on the early perturbation of specific protein–protein interactions within the mitochondria. This methodology forms a blueprint for biomarker discovery that can identify rearrangements of MDM2 protein–protein complexes in drug‐treated cells.